OPTIMALISASI MEDIA PLASTISIN DALAM PENGEMBANGAN KREATIVITAS ANAK USIA DINI - Setiyowati, Eny Setiyowati; Munawaroh, Imroatul (Early Stage, 2024)
This study aims to improve the creativity of early-aged children using the media plastisin.This research is a descriptive qualitative Classroom Action Research (CAR) which by taking the background of  Tk Dharma Wanita 4 Cakul, dongko, Trenggalek. Research subject is student group B Tk Dharma Wanita 4 Cangkul, While research objects are increased creativity early age using the media plastisin.Studies show that the media plastisin can increase child creativity.Increased creativity can be seen by the result of cycle I the growing number of children as expected 50 %, developing very well / optimal 25 % by reaching 75 % presentation on the I cycle it's pretty good.While an increase in the II cycle, number of growing children as expected 58 %, developing very well / optimal 33 % by reaching presentage by 90 %.